If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -9x = 57 + -23x Solving 13 + -9x = 57 + -23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23x' to each side of the equation. 13 + -9x + 23x = 57 + -23x + 23x Combine like terms: -9x + 23x = 14x 13 + 14x = 57 + -23x + 23x Combine like terms: -23x + 23x = 0 13 + 14x = 57 + 0 13 + 14x = 57 Add '-13' to each side of the equation. 13 + -13 + 14x = 57 + -13 Combine like terms: 13 + -13 = 0 0 + 14x = 57 + -13 14x = 57 + -13 Combine like terms: 57 + -13 = 44 14x = 44 Divide each side by '14'. x = 3.142857143 Simplifying x = 3.142857143
| 83-3x=24x+17 | | 5-10x=170-45x | | 62-6x=8x-4x | | 132-5x=4x+24 | | -17-6x=7-10x | | 119-6x=10x+63 | | 4x+29=6x+11 | | 3x+5x=5+x | | 2p+3=4+5p | | 16x^4-2x^2+1=0 | | 4t+3=t-12 | | 7x+7=5x-11 | | 176-4x=23x+23 | | 5-8x=79-22x | | -18-9x=8x+16 | | 2z-6=14-3z | | 3q=12-q | | 7x+24=3x+112 | | 4t+2=17-t | | 4q+3=q+3 | | x^4-8x^3+x-8=0 | | 12-8x=39-29x | | 35+33x=11x+12+22 | | -143-9x=9x+9x | | 3a-1=a+7 | | 7a+2=10 | | 3+5u=2u+12 | | 2x+7x^2=8 | | 6m-1=m+9 | | 2x+7x=4 | | x^3-3x-18=0 | | 4x*57=3x-7 |